Clinical features and echocardiographic findings of isolated foramen ovale restriction in foetuses. (4th July 2022) - Akbaş, Tolga; Demir, Fadli; Erdem, Sevcan; Çağnıs, Berivan; Özlü, Ferda; Büyükkurt, Selim; Özbarlas, Nazan
Abstract: Isolated restrictive foramen ovale (rFO) without complex heart defects is a rare pathology. There may be difficulties in managing this situation, which can lead to right heart enlargement, tricuspid regurgitation and hydrops findings in the foetus. We conducted a retrospective analysis of 8451 foetuses. 7883 (93.2%) had a structurally normal heart or minor heart disease, 18 (0.22%) of which had a diagnosis of isolated rFO. Nine patients with neonatal echocardiographic examination were included in the study. In 8 (88.8%) patients, it was stated that a decision to give birth should be made at the time of presentation. Evaluating postpartum echocardiographic examinations, 7 (77.7%) patients had normal or minor defects. The decision of delivery made at the right time during follow-up is critical to determine the prognosis. IMPACT STATEMENT: What is already known on this subject? The data about the prenatal diagnosis of isolated rFO is limited. What the results of this study add? We conducted a retrospective analysis of 8451 foetuses. 7883 (93.2%) foetuses had a structurally normal heart or minor heart disease, 18 (0.22%) of which had a diagnosis of rFO. Nıne patients with foetal and postnatal follow-up and echocardiographic findings were examined in the study. The group's median gestational age at admission was 35.0 weeks (range: 27.0–39.0 weeks). The delivery decision was made in 8 (88.8%) patients at the time of admission. Evaluating postpartum echocardiographic examinations, 7 (77.7%) patients had normal or minor defects. Additionally, one patient was diagnosed with cardiomyopathy, and the other patient was diagnosed with functional pulmonary atresia. No death occurred in any foetus during follow-up. What the implications are of these findings for clinical practice and/or further research? Isolated rFO, a rare condition in the foetus, is generally well-tolerated in foetal life. However, the right heart enlargement, tricuspid regurgitation, or hydrops findings can be seen in patients. The decision of delivery made at the right time during follow-up is critical to determine the prognosis.